The knowledge, opinion and attitudes of the first year medical students about substance dependence - Altıntaş, Hakan; Temel, Fehminaz; Benli, Esin; Çınar, Güle; Gelirer, Özlem; Gün, Feride Aylin; Kernak, Aygül; Kundakçı, Nevra (Journal of Dependence, 2004)
Objective: This survey was conducted among the first year medical students of Hacettepe University in order to determine their knowledge, opinions and attitudes about substance dependence. Method: Of the total students, 185 participated in the study which was descriptive in nature. The data was collected using questionnaires under observation. Results: Of the students who participated in the study, 42.7% were men, 57.3% were women. Their average age was 18.3 years (SD=0.7, min-max=17-21, mean=18). Of the participants, 52.2% (90 students) said that they had information about substance dependence before the study. Heroin was the substance which was truely known with a high percentage (91.4%, 169 students) by the students, that can lead to substance abuse. LSD had the lowest percentage (44.9%, 83 students) in this respect. Only, 30.9% (56 students) of the students mentioned that they knew a center for treating substance dependents. Of these, 57.7% (130 students) named AMATEM. Of the participants, 76.8% (142 students) believed that everyone could become addicted to substances. Of the students, 61.4% (113 students) described the addicted people as people who need help, and 93.5% (172 students) said that they should be treated. Of the participants 89.7% (165 students) think that addiction to substances is a problem in Turkey. 58.9% of the students said that education should be the priority to avoid substance abuse problem and to help the people who abuse substances. Conclusion: It is understood that the first year medical students of Hacettepe University don’t have enough knowledge about substance abuse. The students thought that the susbstance abusers are ill people and they should be treated.